Headball: Rules and Its Role in Youth Education Based on the UN Youth Declaration on Transforming Education - Mukhamedrakhim Kursabayev (World Scientific Reports, 2024)
The sport of "Headball" represents a new addition to the football family worldwide. The fundamental rule of the game involves controlling the football using only the head. The game is accessible to anyone, regardless of age, gender, or other affiliations. While the rules of "Headball" closely resemble those of "Futsal," there are some distinctions. The development of "Headball" contributes to bringing together the interests of children and youth, serving as an educational tool based on the UN Youth Declaration on Transforming Education and the United Nations 17 Goals - Sustainable Development Goals (Goal 4). This article presents information on the rules of the "Headball" game and emphasizes the need for sports events to unite interests and identify the educational values of the younger generation based on the Youth Declaration on Transforming Education document.